2020
DOI: 10.1186/s13018-020-01597-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effect of a lateral hinge fracture for a medial opening wedge high tibial osteotomy: finite element study

Abstract: Background: This study aimed to investigate the biomechanical effect on the Takeuchi classification of lateral hinge fracture (LHF) after an opening wedge high tibial osteotomy (HTO). Methods: We performed an FE simulation for type I, type II, and type III in accordance with the Takeuchi classification. The stresses on the bone and plate, wedge micromotion, and forces on ligaments were evaluated to investigate stress-shielding effect, plate stability, and biomechanical change, respectively, in three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…In type II LHFs, a rotational deformity is formed and leads to delayed union, nonunion, or correction loss. 28 In addition, 1 biomechanical study 7 reported that a stress-shielding effect because of the increased plate stress and reduced bone stress was observed in cases with type II LHFs. Therefore, close observation of valgus collapse and the status of the bony union is necessary during the rehabilitation period for type II LHFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In type II LHFs, a rotational deformity is formed and leads to delayed union, nonunion, or correction loss. 28 In addition, 1 biomechanical study 7 reported that a stress-shielding effect because of the increased plate stress and reduced bone stress was observed in cases with type II LHFs. Therefore, close observation of valgus collapse and the status of the bony union is necessary during the rehabilitation period for type II LHFs.…”
Section: Discussionmentioning
confidence: 99%
“…Type III fractures are unstable intra-articular fractures because the proximal fragment is only supported by the medial plate. 7 Therefore, we performed screw fixation for type III LHFs, which were mostly diagnosed intraoperatively. In addition, a hinged brace was applied and weightbearing was delayed until 6 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A relative high-stress area appeared near the outside corner and the D-hole of the medial TomoFix plate in HTO, particularly with LHFs in the present study. In the previous FE study [ 15 ], the stress of the plate was also increased, particularly in the T2 and T3 LHFs. The high stress after LHFs can create a crack and then extend to the screw hole after cyclic loading during postsurgical walking without bone healing.…”
Section: Discussionmentioning
confidence: 84%
“…Many studies have investigated LHF incidence after HTO and complications following LHFs. The biomechanical effect of the LHFs on the HTO with medial opening wedge and the bone plate was also revealed [15]. In the study, the stress of the medial plate was increased with the LHFs.…”
Section: Introductionmentioning
confidence: 78%
“…The advantages and shortcomings of the plate adapting techniques, raises the question that “what level of geometrical fit with the underlying bone is appropriate for a HTO locking plate fixation?” The previous studies on the biomechanics of the HTO fixation have often neglected this question and focused on the effects of different plate designs, for example, Puddu (Arthrex Ltd, Naples, FL, USA), 1618 Tomofix (Arthrex Ltd, Naples, FL, USA), 1628 Limmed, 29 Activemotion (Newclip Technics, Haute-Goulaine, France), 26 iBalance (Arthrex, Munich, Germany), 24,26 Contour Lock (Arthrex, Munich, Germany), 24,26 PEEKPower (Arthrex, Munich, Germany), 20,24,26 and LCfit (Corentec, Cheonan-si, South Korea), 23 as well as the screw types 19,22,25,30 and configurations, 27 on the fixation stability. In fact, we found only a single study 31 addressing the influence of plate contouring on the biomechanical performance of the HTO fixation.…”
Section: Introductionmentioning
confidence: 99%